2013
DOI: 10.1093/toxsci/kft271
|View full text |Cite
|
Sign up to set email alerts
|

Coexposure to Phytoestrogens and Bisphenol A Mimics Estrogenic Effects in an Additive Manner

Abstract: Endocrine-disrupting chemicals (EDC) are abundant in our environment. A number of EDCs, including bisphenol A (BPA) can bind to the estrogen receptors (ER), ERα and ERβ, and may contribute to estrogen-linked diseases such as breast cancer. Early exposure is of particular concern; many EDCs cross the placenta and infants have measurable levels of, eg, BPA. In addition, infants are frequently fed soy-based formula (SF) that contains phytoestrogens. Effects of combined exposure to xeno- and phytoestrogens are poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 63 publications
(72 reference statements)
1
38
0
Order By: Relevance
“…These results indicate that BPA and estradiol may be signaling through similar pathways to cause exacerbated migraine-like behaviors. Studies have demonstrated that BPA has the ability to interact with and activate ERalpha, ERβ, and GPR30 (Katchy, et al, 2014, Montes-Grajales and Olivero-Verbel, 2013). Interestingly, a recently published study demonstrated BPA-mediated activation of ERK in a cell model, and the use of a GPR30 antagonist in conjunction with BPA exposure led to suppression of ERK activation (Ge, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that BPA and estradiol may be signaling through similar pathways to cause exacerbated migraine-like behaviors. Studies have demonstrated that BPA has the ability to interact with and activate ERalpha, ERβ, and GPR30 (Katchy, et al, 2014, Montes-Grajales and Olivero-Verbel, 2013). Interestingly, a recently published study demonstrated BPA-mediated activation of ERK in a cell model, and the use of a GPR30 antagonist in conjunction with BPA exposure led to suppression of ERK activation (Ge, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We found that identical genes were regulated by BPA, phytoestrogens, and 17β-estradiol. 29 Although MCF-7 cells also express the AR, PPARα/β/γ, TRα/β, GPER1, and AHR, 3032 we found that the expression of all genes regulated at 24 h BPA treatment were inhibited by co-treatment with the ERα antagonist ICI. 29 This suggests that the transcriptional activity elicited by BPA in these cells was mediated through ERα, and that there were no unique BPA target genes that estrogen did not activate.…”
Section: Tissue- and Cell-specific Effects Of Bpamentioning
confidence: 76%
“…We also demonstrated that BPA and phytoestrogens acted in an additive manner. 29 The additive effect of BPA and phytoestrogens raises concerns that the feeding of phytoestrogen-rich soy-based formula to infants may enhance the effect of BPA exposure.…”
Section: Tissue- and Cell-specific Effects Of Bpamentioning
confidence: 99%
See 1 more Smart Citation
“…BPA acts as an estrogen mimetic and can interact with the ligand-binding domain of ERα (Sengupta et al 2013), increasing cellular proliferation, potentially via reducing the rate of apoptosis (Mlynarcikova et al 2013), and inducing a gene expression profile that clusters with poor breast cancer prognosis (Katchy et al 2014). BPA also interacts with the orphan nuclear receptor, estrogen-related receptor γ (ERRγ; Takayanagi et al 2006), and may also signal via the G-protein-coupled receptor GPER/GPR30 (Pupo et al 2012).…”
Section: Bisphenol Amentioning
confidence: 99%